2023
DOI: 10.1038/s41598-023-44917-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for stroke after hip fracture: a meta-analysis

José María Lamo-Espinosa,
Gonzalo Mariscal,
Jorge Gómez-Álvarez
et al.

Abstract: Hip fractures represent a high burden and are associated with mortality in up to 30% of the cases. Stroke complications can be devastating and increase mortality and disability in elderly patients. This study aimed to determine the overall incidence and risk factors for stroke in patients with hip fractures. A systematic search of the literature using PubMed, EMBASE, Scopus, and Cochrane Collaboration Library databases was carried out. Studies have reported the incidence of stroke in patients > 50 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…36 Moreover, fractures can result in further functional decline, disrupt stroke rehabilitation, and elevate the risk of subsequent stroke. 37,38 The American Heart Association/American Stroke Association and guidelines for adult stroke rehabilitation and recovery recommend a formal fall prevention program during hospitalization for stroke survivors, and that stroke patients discharged to the community participate in exercise programs with balance training to reduce falls. 39 A previous study demonstrated reduced fracture risk with regular exercise following acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…36 Moreover, fractures can result in further functional decline, disrupt stroke rehabilitation, and elevate the risk of subsequent stroke. 37,38 The American Heart Association/American Stroke Association and guidelines for adult stroke rehabilitation and recovery recommend a formal fall prevention program during hospitalization for stroke survivors, and that stroke patients discharged to the community participate in exercise programs with balance training to reduce falls. 39 A previous study demonstrated reduced fracture risk with regular exercise following acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed rehabilitation of stroke survivors is a risk factor for fracture 36 . Moreover, fractures can result in further functional decline, disrupt stroke rehabilitation, and elevate the risk of subsequent stroke 37,38 . The American Heart Association/American Stroke Association and guidelines for adult stroke rehabilitation and recovery recommend a formal fall prevention program during hospitalization for stroke survivors, and that stroke patients discharged to the community participate in exercise programs with balance training to reduce falls 39 .…”
Section: Discussionmentioning
confidence: 99%